Physiochemical properties of reduced-fat duck meat emulsion systems: effects of preemulsification with vegetable oils and duck skin - Tae-Kyung Kim (Poultry Science, 2021)
The effects of commercial vegetable oils and duck skin on quality characteristics of a reduced-fat duck meat emulsion were examined. The cooking loss, emulsion stability, and hardness were lower for emulsions preemulsified with vegetable oils and duck skin (P < 0.05) than for the control. Storage modulus (G′) and loss modulus (G″) of reduced-fat duck meat emulsions treated with corn, grape seed, soy, and olive oils were similar to the values of control; the highest G′ and G″ values were reported for the reduced-fat duck meat emulsion treated with coconut oil. Myofibril protein solubility was the highest for the reduced-fat duck meat emulsion treated with coconut oil and duck skin (P < 0.05). Replacing of pork back fat with different vegetable oils for emulsification may impart superior quality to reduced-fat duck meat emulsion. We recommend preemulsion with vegetable oils and duck skin to enhance the quality characteristics of reduced-fat duck meat emulsion.